Kanišite Hittite: the earliest attested record of Indo-European - Kloekhorst, Alwin (Handbook of Oriental studies, 2019)
part 1. Methodology and Analyses -- Personal Names in the Old Assyrian Texts from Kanis -- The Linguistic Analysis of Personal Names : Methodological Preliminaries -- Phonological Interpretation of the Kanisite Names -- Identifying the Linguistic Background of the Kanisite Personal Names -- Part 2. Kanisite Hittite Personal Names: the Material -- Kanisite Hittite Compound Names -- Other Kanisite Hittite Names -- Excursus 1: Kanisite asie/at (m.) and na/ikilie/at (m.) and the Hittite Verbal System -- Excursus 2 : Kanisite -asue and the Feminine Gender in Hittite and Proto Indo_European -- Part 3. The Linguistic Status of Kanisite Hittite -- Comparing Kanisite Hittite to Hattusa Hittite -- Two Hittite Dialects : Historical Reality